2007
DOI: 10.1016/j.epsl.2007.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The diachroneity of alluvial-fan lithostratigraphy? A test case from southeastern Ebro basin magnetostratigraphy

Abstract: Alluvial-fan strata contain valuable proxy data for kinematic, climatic and sediment-flux phenomena associated with high-relief source regions. Proper application of this data is dependent upon acquisition of accurate high-resolution chronostratigraphic data, best achieved through magnetostratigraphy. Collection of magnetostratigraphic and other proxy data from composite alluvial-fan sections assumes the chronostratigraphic significance of lithostratigraphy. We present the first test of this assumption with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…Because of the autogenic switching of active fan lobes, stratigraphic successions of fan systems accumulate under spatially inhomogeneous patterns of aggradation and non‐deposition that can lead to local stratigraphic incompleteness and lack of chronological correlation between adjacent deposits. The problem has been frequently underestimated in analyses of thick fan successions, due to the common lack of high‐resolution chronostratigraphic data to constrain the age and correlatability of different depositional units (Swanson‐Hysell & Barbeau, ). Recent evidence from Quaternary piedmont fans in California demonstrates that the absence of an incised fan‐head channel favours spatially uniform aggradation and complete resurfacing over time spans in the order of a few thousand years (Dühnforth et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the autogenic switching of active fan lobes, stratigraphic successions of fan systems accumulate under spatially inhomogeneous patterns of aggradation and non‐deposition that can lead to local stratigraphic incompleteness and lack of chronological correlation between adjacent deposits. The problem has been frequently underestimated in analyses of thick fan successions, due to the common lack of high‐resolution chronostratigraphic data to constrain the age and correlatability of different depositional units (Swanson‐Hysell & Barbeau, ). Recent evidence from Quaternary piedmont fans in California demonstrates that the absence of an incised fan‐head channel favours spatially uniform aggradation and complete resurfacing over time spans in the order of a few thousand years (Dühnforth et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Went, ), where the shingled stacking of depositional units does not produce notable textural and facies variations (Beaty, ; Blair, ). As observed by several authors, the main uncertainty in this approach to architectural interpretation is determined by the spatial and temporal overlap between stratigraphic products of high‐frequency climate cycles and autogenic mechanisms, and by the difficulty in obtaining chronologies of sufficient resolution to discriminate between architectural elements (Gloppen & Steel, ; Mustard, ; Swanson‐Hysell & Barbeau, ). Studies of Quaternary systems apply a variety of dating methods to estimate patterns of fan‐surface activity and abandonment (e.g.…”
Section: Autogenic Processes In Alluvial Fansmentioning
confidence: 99%
“…It is worth noting that the compacted accumulation rates obtained for Montserrat (up to 42 cm kyr −1 ) are strikingly higher than average accumulation rates estimated (15–20 cm kyr −1 ) in Priabonian to Oligocene synorogenic alluvial successions in other marginal areas of the SE Ebro Basin (Jones et al ., ; López‐Blanco et al ., ; Swanson‐Hysell & Barbeau, ; as re‐interpreted in Garcés et al ., ; Costa et al ., ). These contrasting patterns of accumulation along the CCR‐Ebro Basin foreland system may be related to differences in subsidence and, therefore, in the structural style.…”
Section: Tectonosedimentary Evolutionmentioning
confidence: 99%
“…Subsidence was distributed along a wider region ahead of the mountain front, resulting in lower average accumulation rates of about 15 cm kyr −1 . Another study in the Gandesa area reported sedimentation rates as high as 32 cm kyr −1 (Swanson‐Hysell & Barbeau (), but we note that these are based on a correlation with the GPTS which is not final as admitted by the same authors (Swanson‐Hysell & Barbeau, ). Despite the criticism of Swanson‐Hysell & Barbeau (, ), we rely on the magnetostratigraphic study of Jones et al .…”
Section: Tectonosedimentary Evolutionmentioning
confidence: 99%
See 1 more Smart Citation